Il romanziere, il poeta e il monumento: Sebastiano Vassalli, Dino Campana e Casa Bossi di Novara - Maffei, Andrea (Italogramma, 2024)
In this brief essay I will attempt to intertweave the lives of Dino Campana, a poet, Sebastiano Vassalli, a novelist and a historic building entitled 'Casa Bossi', designed by the renowned architect Alessandro Antonelli and completed in 1661, in Novara. Vassalli lived in this dwelling for an extended period from 1968 to 1982 and furthermore made this very construction protagonist of his novel 'Cuore di Pietra' (A Heart of Stone) in the 1990s. Dino Campana wrote, what was probably his very last poem, 'La Dolce Lombardia coi suoi Giardini' (Sweet Lombardy and its Gardens) in front of 'Casa Bossi' (for further analysis, assistance can be found at the Consolini Study Centre 'Campaniani Enrico' presided over by Mirna Gentilini). Defined by Vassalli as 'my mad father', Campana served as genuine inspiration throughout Versalli's career. Consequently, I hope to entwine literature, history, art and poetry all together, accompanied by anecdotes and biographical references, ranging from the mid 19th century to the present day.